Liquidity risk and bank financial performance: an application of system GMM approach - Yahaya, Adamu; Mahat, Fauziah; Yahya, M. H.; Matemilola, Bolaji Tunde (Emerald Publishing;, 2022)
Purpose: This study aims to examine the effect of liquidity risk on deposit money banks’ (DMBs) performance in Sub-Saharan Africa. This study also tests the interaction effect of liquidity risk and nonperforming loans on the performance of DMBs’ in Sub-Saharan Africa. Design/methodology/approach: This study uses a two-step system generalized method of moment to test the influence of liquidity risk on DMBs’ performance in Sub-Saharan Africa. A sample of 50 listed banks across six Sub-Saharan African countries, including Nigeria, Ghana, South Africa, Zambia, Kenya and Tanzania, were used. The bank performance proxy used are return on asset and return on equity, while net interest margin is used for robustness check. Findings: The study’s findings reveal a significant and negative association between liquidity risk and bank performance. Moreover, the relationship between the nonperforming loan and bank performance is negative and significant. Furthermore, the interaction effect of liquidity risk and nonperforming loans on bank performance is found to be significantly negative for the two proxies of bank performance. The result is robust for the alternative bank performance measurements and econometric model, which adequately addresses endogeneity tendency. Originality/value: To the best of the researchers’ knowledge, this is one of the earliest empirical studies that examine the effect of liquidity risk on DMBs’ performance across Sub-Saharan African countries. This study further differs from previous studies with the interaction term of liquidity risk and nonperforming loan included in the model.